Activity oriented teaching: efficacy of Vee diagrams and mind-maps on biology scholars’ attitudes and academic achievement - Edarho Oghenevwede Oyovwi; Rita Ewere Chukwuka (Journal of Education and Learning (EduLearn), 2026)
The study investigated the efficacy of Vee diagrams and mind-maps on biology scholars’ attitudes and academic achievement. The study adopted a pretest, posttest planned variation quasi-experimental design. The 276 senior secondary II (SSII) biology scholars made up the study’s sample. The instruments utilized for data collection include biology achievement test (BAT) and biology attitude scale (BAS). Analysis of covariance (ANCOVA) was applied to examine the pretest and posttest ratings at the 0.05 level of significance. The study demonstrated that scholars tutored biology concept with Vee diagrams improve in their achievement compared to scholars tutored using mind-maps, Vee diagrams improve scholars attitude in comparison to those tutored biology using mind-maps, male/female did not in fluence scholars tutored biology using Vee diagrams, male/female scholars tutored in biology using Vee diagram did not differ in their attitude ratings, no effect of male/female on biology scholars instructed using mind-maps, no significant discernible disparity in the attitude ratings of male/female scholars tutored biology using mind-maps.